How can energy prices and subsidies accelerate the integration of electric vehicles in Brazil? An economic analysis - da Silva, Ricardo Emilio [UNESP]; Sobrinho, Pedro Magalhães [UNESP]; de Souza, Teófilo Miguel [UNESP] (Elsevier, 2018)
A sensitivity analysis indicates that the variables that most influence the payback period on purchases of battery electric vehicles are gasoline prices and financial incentives granted in the form of an exemption from the annual tax payment. Currently, the arithmetic mean value of the payback period for the purchase of BEVs is 24.23 years in 27 analyzed state capitals, suggesting broad-based adoption remains years away.
Keywords: Battery electric vehicles; Brazil; Energy planning; Energy prices; Incentives